Protective glass plate of display device - KASHIMA IZURU; KOBAYASHI YUSUKE (2017)
The invention provides a protective glass plate of a display device. The glass plate includes a main flat surface, an edge surface orthogonal to the main flat surface, and a chamfered surface adjacent to the main flat surface and the edge surface. In a cross-sectional surface of the glass plate that is orthogonal to the edge surface and that is orthogonal to the main flat surface, the chamfered surface has a curvature radius (r2) greater than or equal to 50 [mu]m at an intersection point between the chamfered surface and a straight line inclined 45 degrees with respect to the main flat surface and a curvature radius (r1) ranging from 20 [mu]m to 500 [mu]m at an intersection point between the chamfered surface and a straight line inclined 15 degrees with respect to the main flat surface. 种显示器的防护玻璃板，其具有主平面、相对于该主平面垂直的端面、及形成于所述主平面和所述端面之间并与所述主平面和所述端面相邻的倒角面，其中，在相对于所述主平面和所述端面垂直的剖面中，所述倒角面在与相对于所述主平面的倾角为15°的直线相切的切点处的曲率半径(r1)为20μm～500μm，且所述倒角面在与相对于所述主平面的倾角为45°的直线相切的切点处的曲率半径(r2)为50μm以上。